The experimental demonstration of a low-cost 37-horn focal-plane array consisting of smooth-walled multiple flare-angle horns fabricated by direct drilling - J. Leech (2018)
In previous work, we have described novel smoothwalled multiple flare-angle horns designed using a genetic algorithm. A key feature of these horns is that they can be manufactured very rapidly and cheaply in large numbers, by repeated direct drilling into a single plate of aluminium using a shaped machine tool. The rapid manufacturing technique will enable the construction of very low cost focal-plane arrays, offering an alternative to conventional electroformed corrugated horn arrays. In order to experimentally demonstrate the new technology, we constructed a 230 GHz focal-plane array comprising 37 smooth-walled horns fabricated by direct drilling. We present the measured beam patterns for a large sample of these horns across the array, demonstrating the suitability of our manufacturing techniques for large format arrays. We have measured the cross coupling between adjacent feeds and have shown that it is negligible. We also present high quality beam patterns measured for a much smaller 700 GHz horn, showing the promise of extending this technology to THz frequencies.